Development of an Automatic Monitoring System for the Assessment of Water Quality in Galing River, Kuantan - Wan Faizal, Wan Ishak (Institute of Research Engineers and Doctors, USA, 2014)
The common approach in monitoring river water quality consists of manual sampling and transport the sample to the laboratory for chemical analysis. This approach although it is non-technical and easily reproducible, however it is increasingly difficult if the location of sampling located in remote locations and far away from the urban area. An effective water quality monitoring must be implemented for water resources management in order to overcome this severe condition towards the watershed. Without accurate and intensive data acquisition, the condition of water resources cannot be adequately assessed, effective preservation and remediation programs cannot be run and the evaluation to the monitoring program cannot be successfully evaluated. In this study. Generally, this instrument is used to measure about 10 of water quality parameters which are pH, dissolved oxygen, electric conductivity, turbidity, ammoniacal nitrogen, nitrite, nitrate, phosphate and biochemical oxygen demand. These parameters will be compared according to the standard method APHA 1948.